The war trail of Big Bear, being the story of the connection of Big Bear and other Cree Indian chiefs and their followers with the Canadian North-west rebellion of 1885, the Frog Lake massacre and events leading up to and following it, and of two month's imprisonment in the camp of the hostiles - Cameron, William Bleasdell, 1862-1951. (Boston, Small, Maynard, 1927)
"First published, 1926. Second edition (revised) 1927." Mode of access: Internet.